THE ROLE OF COLLOCATIONS IN THE ENGLISH TEACHING AND LEARNING - Amir Abushaev (Journals Park Publishing, 2023)
English collocations are a considerable part of the English language. Collocations are commonly used in English speech and writing and are considered an indispensable factor in the proficiency of the learners of English. Acquiring collocations is crucial, challenging, and problematic to non-native English speakers. Nevertheless, it is noticed that collocations are still underestimated in different EFL contexts, which may hinder English learners' fluency in speaking and writing. This article aims at reviewing the literature relating to the term collocations. First, the paper presents the definitions of the term collocations. Next, the paper reviews the studies in the field of collocations. Finally, the paper states some rationales for the inclusion of collocations in English teaching and learning.
Keywords: collocations, EFL, contexts, fluency, inclusion, lexical collocation.